Nanotechnology and Tumor Imaging: Seizing an Opportunity - Daniel C. Sullivan; Mauro Ferrari (Molecular Imaging)
Nanoparticles, labeled with a signaling moiety for in vivo imaging, and one or more ligands for molecularly targeted specificity, hold considerable promise in oncology. Nanoparticles can serve as modular platforms, from which a wide variety of highly sensitive and specific imaging agents can be created. For example, many hundreds or thousands of atoms that provide imaging signals, such as radioisotopes, lanthanides, or fluorophores, can be attached to each nanoparticle, to form imaging agents that would provide higher sensitivity that can be obtained from agents based on small molecules. Similarly, many copies of targeted ligands can be attached to nanoparticles to markedly inrease specific binding. Drugs or therapeutic isotopes can be added to create multifunctional nanoparticles. Appropriately labeled and targeted nanoparticles could lead to a paradigm change in which cancer detection, diagnosis, and therapy are combined in a single molecular complex.